MODELING THREATS AND MIGRATION AMONG MINORITIES - ShahzadFarid , Dr. Muhammad Zahid , Dr. Sarfraz Khan , Sajjad Hussain (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The present study aimed to develop model of perceived threats to religious minorities and their intentions to migrate from Pakistan. We selected 275 respondents randomly from District Multan. Structure equation model revealed that social, cultural and religious threats were associated with intentions of migration among minorities. Social threat, consisted of life insecurity, hostility of majority and social exclusion, is stronger predictor of intentions to migrate from Pakistan (p<.001). Additionally, it was suggested that government officials should encourage cross-religious participation to produce culturally pluralistic communities in Pakistan. The law enforcement agencies should control extra-judicial murders of minorities and promote national collectiveness regardless of religious diversity.